Exploring the Formation of Methodological Beliefs among English Teachers in Chile - Victor Birkner; Tamara Cortes; Rosa Delicio (Smart Society, 2023)
The purpose of this single-participant case study, conducted through purposeful sampling and semi-structuredinterviews,is to gain a deep understanding of how Chilean English teachers construct the beliefs that inform their methodology in disadvantagedcontexts.Theinvestigation was guided by the followingquestions: 1. How  do  teachers  construct  their  beliefs  about  English  language  teaching methodology? 2. What types of factors are involved in the construction of those beliefs? The  data  were meticulously collectedand  subsequently thematically analysed. The analysis   identified   six   themes:previous   experience,   social interaction,   teaching   materials,   attitudes   towards   mistakes,   teacher   self-evaluation,  and  challenges  outside  the  classroom.  Although  the  study  confirms the findings of previous studies, two relevant themes, attitudes towards mistakes and  challenges  outside  the  classroom,  emerged  to  contribute  to  the  theoretical development of teachers’methodological beliefs. These two themes stand out as they shed light on how teachers of English in Chile maximisethe classroom time to teach Englishandtreatmistakeswith a positive attitude as a way topromote adaptability and resilience in contexts where speakingEnglish outside the schoolis extremely limited. Unlike previous studiesthat examinedclassroom dynamicsand mistakes in isolation, our study offers fresh insights into the complex world of  methodological  beliefs  among  Chilean  teachers  of  English  in disadvantagedcontexts.Future research should incorporate observations alongside interviews, increase participant numbers for deeper insights, and explore how attitudes and external challenges influence methodology beliefs in ELT